(untitled) (Solukhumbu Multiple Campus Research Journal, 2024)
The development of teacher agency in teaching academic subjects in English within community schools has become a critical global issue, including in Nepal. This study examines how teachers create agency through translanguaging practices while implementing the English Medium Instruction (EMI) policy in Nepal’s multilingual classroom context. The study employed an ethnographic research design within a qualitative research approach to explore the ideas and experiences of three Basic-level (Grade VI-VII) teachers. Data were collected from three different EMI community schools through in-depth interviews, classroom observations, and field notes. The study found that teachers in EMI community schools in Nepal exercise their agency by employing translanguaging practices such as using bilingual textbooks, integrating students’ mother tongues, and facilitating comprehension during examinations. These strategies help teachers navigate linguistic challenges, making EMI classrooms more inclusive and supportive for multilingual students. The findings highlight the need for policies and professional development programs that support bilingual and translanguaging practices to enhance learning outcomes in multilingual EMI classrooms.